2015
DOI: 10.5551/jat.28647
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition of Phosphate-Induced Calcification in a Rat Aortic Tissue Culture Model

Abstract: Aim: High phosphorus conditions promote vascular calcification (VC) in both chronic kidney disease (CKD) patients and experimental models. However, the composition of medial calcification has not been accurately determined, so the objective of this study was to evaluate the mineral composition of calcification in a tissue culture model, not a cell culture system. Methods: Aortic rings obtained from male Sprague-Dawley rats were incubated in serum-supplemented medium for 10 days. The inorganic phosphate (Pi) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…Thus, the relevant value for the onset of spontaneous precipitation should be that of ACP supersaturation (which depends on ACP solubility and the ionic product of the ions forming the ACP precipitate), rather than that of HAP, as it has been argued for the in vivo condition [ 22 ]. While HPO 4 2- is the only phosphate species in DCPD, several characterization techniques, such as 31 P NMR [ 23 ] and X-ray diffraction, have shown that ACP [ 24 ] is mostly, if not only, composed of PO 4 3- , which concurs with a recent report on calcification in vitro that used massive calcification [ 25 ]. This is crucial for predicting precipitation at a certain pH, because the concentration of HPO 4 2- barely changes in the pH range of interest (7.4–8.7), so DCPD supersaturation is not modified.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the relevant value for the onset of spontaneous precipitation should be that of ACP supersaturation (which depends on ACP solubility and the ionic product of the ions forming the ACP precipitate), rather than that of HAP, as it has been argued for the in vivo condition [ 22 ]. While HPO 4 2- is the only phosphate species in DCPD, several characterization techniques, such as 31 P NMR [ 23 ] and X-ray diffraction, have shown that ACP [ 24 ] is mostly, if not only, composed of PO 4 3- , which concurs with a recent report on calcification in vitro that used massive calcification [ 25 ]. This is crucial for predicting precipitation at a certain pH, because the concentration of HPO 4 2- barely changes in the pH range of interest (7.4–8.7), so DCPD supersaturation is not modified.…”
Section: Discussionsupporting
confidence: 77%
“…Many aspects regarding the complex process of vascular calcification and phenotypic remodeling secondary to CKD and uremia remain unanswered. The process has been studied using different in vitro models, including intact vessels (Shroff et al, 2008 ), aortic rings (Lomashvili et al, 2004 ; Sonou et al, 2015 ), or dispersed VSMC, mainly obtained from bovine or rat thoracic aorta (Chen et al, 2006a ; Villa-Bellosta et al, 2007 ; Hortells et al, 2015 ). In spite of the limitations associated with cultured VSMC, such as the lack of extracellular elastin fibers (Lin et al, 2011 ) and the diversity of phenotypes that can co-exist in culture (Patel et al, 2016 ), this model has been extensively used to study vascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, сниженный уровень ингибиторов эктопической кальцификации фетуина-А и альбумина в крови также ассоциирован с повышенным риском развития ишемической болезни сердца [4,5]. В то же время свободные ионы кальция и фосфора могут приводить к прямой кальцификации средней оболочки сосудов (медии), однако не вызывают собственно атеросклероза [6,7] -хронического воспалительного процесса, ха-ОБЗОРНЫЕ СТАТЬИ VOL. 5, № 1, 2020 ® рактеризующегося формированием гетерогенных бляшек из клеток, внеклеточного матрикса и липидов во внутренней оболочке артерий [8,9].…”
Section: природа и биологический смысл кальций-фосфатных бионовunclassified